Distal Biceps Reconstruction With an Alternative Technique for Tendon Tensioning and Fixation: A Case Report. Issue 2 (April 2021) - Leite, Maria João; Silva, Miguel Relvas; Sousa, António; Vieira, Alberto; Neves, Nuno; Ribeiro da Silva, Manuel
Abstract : Case: A 41-year-old right-handed male patient presented to our institution with a chronic distal biceps rupture after failed primary surgery 6 months previously. We performed a reconstruction with semitendinosus autograft fixed proximally with a Pulvertaft weave and distally with a cortical button plus interference screw. The patient showed complete pain resolution and excellent functional results. Conclusion: This is the first case described with the use of a cortical button plus interference screw distally for distal biceps reconstruction after chronic distal biceps rupture. The option of doing the Pulvertaft proximally first also allowed us to fine-tune the final graft tension.